Mechanism of polarization fatigue in BiFeO3 : the role of Schottky barrier - Zhou, Yang (2014)
By using piezoelectric force microscopy and scanning Kelvin probe microscopy, we have investigated the domain evolution and space charge distribution in planar BiFeO3 capacitors with different electrodes. It is observed that charge injection at the film/electrode interface leads to domain pinning and polarization fatigue in BiFeO3. Furthermore, the Schottky barrier at the interface is crucial for the charge injection/accumulation process. Lowering the Schottky barrier by using low work function metals as the electrodes can also improve the fatigue property of the device, similar to what oxide electrodes can achieve.